2003
DOI: 10.1046/j.1365-294x.2003.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA sequences reveal extensive cryptic diversity within a western American springsnail

Abstract: We analysed cytochrome c oxidase subunit I and NADH dehydrogenase subunit I sequence variation among 29 populations of a widely ranging southwestern springsnail (Pyrgulopsis micrococcus) and 18 regional congeners. Cladistic analyses of these sequences depict P. micrococcus as a polyphyletic composite of five well-supported clades. Sequence divergences among these clades and subclades imply the possible occurrence of as many as seven or eight cryptic species in addition to P. micrococcus. Our finding that P. mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 34 publications
10
118
2
Order By: Relevance
“…COI variation in E. hubrichti is relatively low compared with levels of variation in this gene region in other gastropod species (e.g., Holland & Hadfield 2002;Liu et al 2003), but those studies focused on species with much broader geographic ranges than E. hubrichti. The relatively low level of sequence variation within the species could be due to a number of factors.…”
Section: Discussionmentioning
confidence: 99%
“…COI variation in E. hubrichti is relatively low compared with levels of variation in this gene region in other gastropod species (e.g., Holland & Hadfield 2002;Liu et al 2003), but those studies focused on species with much broader geographic ranges than E. hubrichti. The relatively low level of sequence variation within the species could be due to a number of factors.…”
Section: Discussionmentioning
confidence: 99%
“…Partial sequences of mitochondrial cytochrome c oxidase subunit I (COI) and NADH dehydrogenase subunit I (NDI) were obtained. These regions were selected because they have proven useful in resolving relationships within Pygulopsis (Hershler and Liu, 2004;Hershler et al, 2003a,b;Liu et al, 2003) and among other members of the family Hydrobiidae (Wilke and Davis, 2000;Wilke et al, 2001). Seven hundred and ten base pairs of COI and 550 bp of NDI were amplified via the polymerase chain reaction using the primers LCO1490 and HC02198 (Folmer et al, 1994) and ND43F and RND592F (Liu et al, 2003).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Our ongoing study of the molecular systematics of Pyrgulopsis has determined that other traditional groupings of these snails also appear to be composites of divergent lineages and need to be reevaluated with the aid of more robust morphological datasets (in preparation; also see Liu et al, 2003).…”
Section: Taxonomic Implicationsmentioning
confidence: 99%
“…To select an appropriate evolutionary model of nucleotide substitution for each nucleotide fragment, the approach of Minin et al (2003) as implemented in the Perl script DT-ModSel was used. In contrast to the likelihood-ratio tests implemented in MrModeltest 2.2 (Nylander, 2004), this approach of performance-based model selection uses the Bayesian information criterion and considers the relative branch-length error as a performance measure in a consistent framework with penalty for overfitting based on decision theory (Minin et al, 2003). MRBAYES was run for 10 6 generations, submitting the two gene regions separately as well as both together.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…In a study of the cryptic diversity of Tetramorium ants in the western Palearctic, Schlick-Steiner et al (2006) found interspecific divergences for the CO I gene ranging from 4.0 to 10.6 %. Liu et al (2003) investigated cryptic species diversity within the western American springsnail Pyrgulopsis micrococcus and found uncorrected p-distances of the CO I gene among lineages from 3.69 to 10.6 %. Our phylogenetic analyses provided some evidence for distinct species also within C. alpina.…”
Section: Genetic Diversity and Cryptic Speciesmentioning
confidence: 99%